Analisis Konten Pemasaran Islami Pada Akun Instagram Siswa Siswi Sma Islam An Nizam Medan - Gusti Oka Widana; Muhamad Umar Mucktar; Iin Gunawan (ITB AAS INDONESIA Surakarta, 2023)
Access to social media has become a vital need around the world, especially for the younger generation. The Instagram platform is one of the most popular social media in Indonesia and is widely used by high school students. Therefore, the leadership of An Nizam Islamic High School (SMAI) Medan issued a directive for students to wisely use social media, especially Instagram and appealed to students to promote activities carried out at school with the aim of promoting the good name of the school institution, but still upholding Islamic values. Using content analysis of 33 posts by the students of An Nizam Islamic High School on Instagram during the January-March 2022 period, it was found that most of the students' posts were in accordance with the appeal of the SMAI An Nizam leadership. Most postings also use a soft-sell approach which according to the literature is more effective in marketing through social media. The significance of this study lies on the illustration of how social media can be used to Islamic compliance marketing content.